Maturing leadership : how adult development impacts leadership - Reams, Jonathan (Emerald Publishing Limited, 2020)
We've known for years now that demands on leaders are only increasing. Yet we have lacked widely understood, empirically grounded and rigorous ways to support the development of adequate maturity of heart, complexity of mind and skilful practice for leaders to meet these demands. Over the past three decades, a growing number of scholars and practitioners have explored the value of a developmental approach to these issues. In Maturing Leadership, Jonathan Reams brings together a cast of expert contributors to introduce this work to a wider audience. While this approach has previously been on the margins of mainstream leadership development research, Reams brings it to the centre, moving beyond the clichéd characterizations of 'inner work' to bring a finer granularity, precision and rigor to the subjective workings of leaders. The chapters explore how applying insights from the field of constructivist cognitive development can be a key driver for supporting improvements in how we approach leadership development. For researchers and students of leadership, this is an essential addition to the leading theories of developmental approaches to leadership. Increasing complexity in the world is not a passing fad, and the need for leaders to grow in the maturity and sophistication of their responses is a long-term need.